Pendampingan Relawan Sebagai First Responder Kecelakaan Lalu Lintas - Indri Wahyuningsih; Alvian Umar Yuviter (PT FORMOSA CENDEKIA GLOBAL, 2022)
The increase in emergency conditions in the pre-hospital area is not in line with the availability of medical personnel. Therefore, several volunteer communities were formed whose function was to collaborate with ambulances and firefighters in handling emergencies at the pre-hospital. The background of non-health education is a demand for volunteers to continue to update scientific and emergency skills. One of the initial abilities of volunteers in identifying the emergency level of KLL victims at the pre-hospital will determine the next intervention in the hospital. The act of assessing and identifying the emergency of the victim in the pre-hospital area is called triage. Triage is a decision-making process in prioritizing the needs and therapy given to patients based on the level of urgency. In its application, triage guidelines are important for triage officers in determining the success of interventions and medical management for patients because they can be used as a reference in determining patient emergency actions. Failure to determine the appropriate priority level based on triage will result in delayed intervention in critically ill patients so that it will have an impact on worsening conditions that can lead to morbidity and mortality.